Sound intensity: state-of-the art in noise control of buildings - A. COPS (Archives of Acoustics)
This paper summarizes the progress that has been made in the application of sound intensity techniques related to the research of sound transmission loss in building acoustics. The modern development of sound intensity instruments began with the discovery of the fast Fourier transform and with the develpoment of techniques for filtering electrical signals using digital techniques. It was only after these techniques became well established, that instruments and procedures for the determination of sound intensity became available for laboratory and in situ measurements. Applications for these instruments and procedures quickly followed and are still pursued today. In this paper some of these developments are discussed, with emphasis on those directly related to sound transmission loss in buildings.